A method for preparing an alumina carrier
By adding microsphere expansion agent to the alumina support and extruding and reaming holes, a penetrating bimodal pore structure is formed, which solves the problems of the existing alumina support's orifice blockage and insufficient mechanical strength, and improves the life and activity of the catalyst.
Patent Information
- Application Number
- CN202210038135.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-13
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-01-13
AI Technical Summary
When existing alumina carriers treat heavy oil, the orifice is blocked and the mechanical strength is insufficient, resulting in a short catalyst life and a rapid increase in the pressure drop of the device.
By adding microsphere expansion agent to the alumina dry adhesive powder, and using the thickened orifice plate of the extruder and controlling the temperature and pressure, moderately controllable hole expansion is carried out to form a through-bian bimodal pore structure.
The high mechanical strength of the alumina support and the appropriate 100-nanometer pore distribution are achieved, and the demetalization activity and life of the catalyst are improved.
Smart Images

Figure CN116474751B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing an alumina carrier, in particular to a method for preparing an alumina carrier suitable for a hydrogenation catalyst in the petrochemical industry. Background Art
[0002] As crude oil deteriorates, heavy oil processing has become a problem that must be solved by the oil refining industry. As the core technology of heavy oil upgrading, hydrogenation technology mainly removes various impurities in heavy oil through hydrogenation reaction. Metal impurities are mainly enriched in colloid asphaltene, and metal-containing asphaltene molecules can reach ten nanometers. Therefore, for existing alumina carriers, their pores are mainly concentrated between 2 and 12 nm. Therefore, asphaltene molecules are severely controlled by internal diffusion and are easily concentrated on the outer surface of the catalyst to react, resulting in serious pore blockage, which in turn causes a rapid increase in pressure drop and affects the normal operation of the device. Therefore, the residue oil hydrogenation catalyst is required to have a large number of hundreds of nanometer-level pores suitable for the diffusion reaction of asphaltene molecules.
[0003] The existing macroporous alumina carrier cannot meet the requirement of directly generating pores at the hundred-nanometer level, so it is a good choice to expand the existing alumina carrier to form a pore size distribution with bimodal pores at the ten-nanometer level and the hundred-nanometer level. However, whether a physical pore expander or a chemical pore expander is used, the existing pore expansion means have problems such as low efficiency of the pore expander, the need for a higher proportion of pore expanders, poor penetration of super-large pores, and the formation of ink bottle-shaped pores, which leads to a decrease in the mechanical strength of the catalyst. For example, CN 102861615B discloses a method for preparing an alumina carrier, which uses pseudo-boehmite, an extrusion aid, a chemical pore expander, an ammonium salt, a physical pore expander carbon black powder, and water to mix and knead extruded strips, but the pores formed by thermal decomposition of the ammonium salt and the holes formed by ablation of carbon black have poor penetration and low mechanical strength, and the utilization efficiency of the pore expander is low. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a method for preparing an alumina carrier. The alumina carrier prepared by the method has a through bimodal pore structure adjustable within a certain range, has a high proportion of 100-nanometer pores, can meet the diffusion requirements of macromolecular substances, and has the characteristics of high demetallization activity and long catalyst life when applied to residual oil hydrogenation reaction.
[0005] The present invention provides a method for preparing an alumina carrier, comprising the following steps:
[0006] (1) Mix the aluminum oxide dry glue powder and the microsphere expansion agent evenly;
[0007] (2) kneading and stabilizing the materials after mixing in step (1);
[0008] The forming equipment is an extruder; the extrusion head of the extruder is a thickened orifice plate; the thickness of the thickened orifice plate is 5 cm to 50 cm;
[0009] (3) Drying and calcining the molded product obtained in step (2) to obtain an alumina carrier.
[0010] According to the present invention, the microsphere expansion agent in step (1) has a core-shell structure, wherein the shell is a thermoplastic acrylic polymer and the core is a hydrocarbon. The microsphere expansion agent in step (1) is a high temperature type. The shell temperature limit of the microsphere expansion agent in step (1) is 155 to 210°C, preferably 160 to 185°C; the initial volatilization temperature of the core hydrocarbon is 110 to 145°C, preferably 120 to 135°C. The volume fraction of the core hydrocarbon volume to the shell volume is 0.0002% to 0.5%, preferably 0.002% to 0.005%.
[0011] According to the present invention, the particle size of the microsphere expansion agent in step (1) is 1 μm to 100 μm, preferably 5 μm to 50 μm.
[0012] According to the present invention, the microsphere expansion agent in step (1) can be a commercial product or prepared according to the prior art. The commercial product can be at least one of Clocell high temperature foaming microspheres of POLYCHEM Company of the United States and Expancel DU series high temperature foaming microspheres of Nouryon Company of Switzerland. For example, the product models of Clocell high temperature foaming microspheres of POLYCHEM Company of the United States are 186DU20, 180DU25, 186DU35, 186DU45, and for another example, the product models of Expancel DU series high temperature foaming microspheres of Nouryon Company of Switzerland are 920DU20, 920DU40, 920DU80, 920DU120, etc.
[0013] According to the present invention, preferably, the properties of the microsphere expansion agent in step (1) have at least one of AD:
[0014]
[0015]
[0016] According to the present invention, preferably, the microsphere expansion agent in step (1) has at least one of the following properties: EH:
[0017] serial number Particle size / μm Core initial volatile temperature / ℃ Shell temperature limit value / ℃ E 5~9 120~145 155~175 F 10~16 123~133 168~178 G 18~24 123~133 180~195 H 28~38 123~133 190~207
[0018] According to the present invention, the weight of the microsphere expansion agent added in step (1) is 2% to 30% of the weight of the alumina dry rubber powder, preferably 3% to 15%.
[0019] According to the present invention, water, preferably deionized water, needs to be added in step (1); the amount of water added is 70% to 160% of the weight of the aluminum oxide dry rubber powder, preferably 110% to 130%. Water is added together with other raw materials in step (1).
[0020] According to the present invention, an extrusion aid can be added in step (1), and the extrusion aid is one or more of sesbania powder, cellulose, polyvinyl alcohol, polyacrylamide, methyl cellulose, and hydroxypropyl methyl cellulose; the amount of the extrusion aid added is 1% to 5% by weight of the alumina dry rubber powder, preferably 2% to 4%. The extrusion aid is added together with other raw materials in step (1).
[0021] According to the present invention, a peptizing agent may be added in step (1), wherein the peptizing agent is one or more of nitric acid, citric acid, sulfuric acid, acetic acid, and hydrochloric acid, and the amount added is 1% to 5% by weight of the alumina dry glue powder, preferably 2% to 3%. The peptizing agent is added together with the other raw materials in step (1).
[0022] According to the present invention, the stable molding in step (2) is extrusion molding; the stable molding process should be carried out in a high-temperature resistant molding equipment capable of measuring material temperature, cooling, and heating. The high-temperature resistant temperature range of the molding equipment is 100°C to 350°C, preferably 120°C to 300°C.
[0023] According to the present invention, the forming equipment for the stable forming process is an extruder; further, the extruder includes an extruder body: according to the order of the material passing, the extruder body includes a feeding device, an extrusion system, and an extrusion head in sequence. The extrusion head is preferably a thickened orifice plate. The thickness of the thickened orifice plate is 5cm to 50cm, preferably 10cm to 30cm. When the extruder is working, the material enters the extruder through the feeding device, is compressed by the extrusion system, and finally is extruded through the extrusion head for stable forming.
[0024] According to the present invention, the stable forming in step (2) is achieved by an extruder head device. The degree of stable forming is determined by the length of the extruder head.
[0025] According to the present invention, the temperature of the stable molding process in step (2) should be controlled to be 10°C to 50°C higher than the initial volatilization temperature of the microsphere expansion agent core in step (1), preferably 20°C to 40°C.
[0026] According to the present invention, the temperature of the stable molding process in step (2) should be controlled to be 5°C to 40°C higher than the temperature limit of the shell of the microsphere expansion agent in step (1), preferably 5°C to 25°C.
[0027] According to the present invention, preferably, the pressure during the stable molding process in step (2) should be controlled to be 100 kg / cm 2 ~180kg / cm2 .
[0028] According to the present invention, the drying in step (3) is performed at 50-150°C for 1h-5h; the calcination is performed at 500-1000°C for 2h-5h, preferably 800-1000°C.
[0029] According to the present invention, the alumina carrier has a through bimodal pore structure, and the pore volume of the alumina carrier is 0.8-1.3 mL / g; the pore volume occupied by pores with a pore diameter of 1-15 nm is 40%-94% of the total pore volume; the pore volume occupied by pores with a pore diameter of 100-1000 nm is 5%-59% of the total pore volume.
[0030] According to the present invention, preferably, the pore volume of the alumina carrier is 0.9-1.2 mL / g. The pore volume of pores with a pore diameter of 1-15 nm accounts for 40%-73% of the total pore volume; the pore volume of pores with a pore diameter of 100-1000 nm accounts for 25%-59% of the total pore volume.
[0031] According to the present invention, in the alumina carrier, the concentration of the macropore distribution with a pore diameter of 100 to 1000 nm can be adjusted, for example, the macropore distribution is concentrated in 100 to 500 nm, for example, the macropore distribution is concentrated in 100 to 200 nm, 200 to 500 nm, 400 to 800 nm, 100 to 220 nm or 240 to 500 nm, etc.
[0032] According to the present invention, the specific surface area of the alumina carrier is 80 to 300 m 2 / g, preferably 100 to 180 m 2 / g.
[0033] According to the present invention, the mechanical strength of the alumina carrier is 10-30 N / mm, preferably 12-20 N / mm.
[0034] According to the present invention, the shape of the alumina carrier can be a conventional shape in the art, such as a columnar, spherical, ellipsoidal, cylindrical, bar, impeller, toothed ball, clover, four-leaf clover and other special shapes, and holes can be opened on it, and grooves can be provided on the outer surface.
[0035] According to the present invention, the alumina carrier can be used in a residual oil hydrogenation catalyst. When used as a hydrogenation catalyst, the active metal component can be loaded by means commonly used in the art. The active metal is a metal of Group VIB and / or Group VIII, the metal of Group VIB is preferably molybdenum and / or tungsten, and the metal of Group VIII is preferably cobalt and / or nickel. Based on the mass of the carrier, the content of Group VIB metal oxide is 1% to 20%, and the content of Group VIII metal oxide is 0.1% to 8%.
[0036] According to the present invention, the residual oil hydrogenation catalyst prepared by using an alumina carrier is suitable for treating residual oil with the following properties: Ni+V content is 20 to 150 ppm. The content is by mass.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] In the present invention, in the preparation method of the alumina carrier, a small amount of microsphere expansion agent is added to the alumina dry rubber powder, and the microsphere expansion agent is controlled by controlling the appropriate temperature during extrusion molding through the extruder shape limitation and the extrusion pressure to perform moderate and controllable pore expansion, and the re-expansion caused by the sudden pressure drop at the extrusion outlet is ensured by the stabilization section to not affect the carrier shape and mechanical strength, thereby obtaining an alumina carrier with adjustable through bimodal pore distribution and high mechanical strength. The method of the present invention avoids the problems of large amount of pore expansion agent, poor mechanical strength, poor penetration of super-large pores, and formation of ink bottle-shaped pores when using traditional pore expansion agents to expand the pores to obtain 100-nanometer pores. The alumina expanded by the microsphere expansion agent is particularly suitable for use as a heavy oil hydrogenation catalyst carrier. The hydrogenation catalyst obtained by loading the active metal on the alumina carrier has the characteristics of high demetallization activity and long catalyst life when used in the residual oil hydrogenation reaction.
[0039] The alumina carrier of the present invention has a through bimodal pore structure adjustable within a certain range, has a high proportion of 100-nanometer pores, and can meet the diffusion requirements of macromolecular substances. The alumina carrier is suitable for use as a heavy oil hydrogenation catalyst carrier. The hydrogenation catalyst obtained by loading the active metal component on the alumina carrier has the characteristics of high demetallization activity and long catalyst life in the residual oil hydrogenation reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is a schematic diagram of the structure of an extruder in the preparation method of the present invention;
[0041] Figure 2 It is a schematic diagram of the thickened orifice plate structure of the extruder in the preparation method of the present invention;
[0042] Description of main reference numerals:
[0043] 1-Feeding device; 2-Extrusion system; 3-Thickened orifice plate. DETAILED DESCRIPTION
[0044] The effects and results of the method of the present invention are further described below with reference to the embodiments, but are not limited to the following embodiments.
[0045] In the present invention, the pore volume and pore distribution are measured by mercury intrusion method; the mechanical strength is measured by a particle strength tester; and the specific surface area is measured by BET method.
[0046] In the present invention, the microsphere expansion agent of Example 4 is Clocell high-temperature foaming microspheres produced by POLYCHEM Company of the United States, model 180DU45, the particle size of this batch is 45 μm, the initial volatilization temperature of the core hydrocarbon is 125°C, and the temperature resistance limit value of the outer shell thermoplastic acrylate polymer is 180°C.
[0047] In the present invention, the microsphere expansion agent of Examples 1, 2, 3, 5, and 6 is Expancel DU series high-temperature foaming microspheres of Nouryon Company of Switzerland, model 920DU20, the average particle size of this batch is 7 μm, the initial volatilization temperature of the inner core hydrocarbon is 130°C, and the temperature resistance limit value of the outer shell thermoplastic acrylate polymer is 170°C.
[0048] In the present invention, the pressure of the molding process in each example is controlled to be 140 kg / cm 2 .
[0049] In the present invention, the Ni removal rate / % and V removal rate / % of the embodiments and comparative examples are:
[0050] Ni removal rate / %=1-(Ni mass content in produced oil / Ni mass content in raw oil)×100%;
[0051] V removal rate / %=1-(V mass content in the produced oil / V mass content in the raw oil)×100%.
[0052] In the present invention, the thickness of the orifice plate refers to the length of the orifice plate along the direction in which the extruded holes on the orifice plate penetrate.
[0053] In the present invention, the extruder used in Examples and Comparative Examples 1 to 5 is as follows: Figure 1 The difference between the comparative example 5 and the extruders in the other examples is that the thickness of the orifice plate is different.
[0054] The specific implementation mode of the present invention is as follows: the material enters the extruder through the feeding device 1, is compressed through the extrusion system 2, and finally is stably formed and extruded through the thickened orifice plate 3 to obtain the target product.
[0055] Example 1
[0056] Weigh 3g of 920DU20 microspheres, the volume fraction of the hydrocarbon core to the volume fraction of the spherical shell of the thermoplastic acrylate polymer is 0.002%. Mix the microspheres with 100g of alumina dry powder and 120g of deionized water and knead them thoroughly. Put the kneaded materials into a high-temperature extruder that can measure, cool and heat the materials for extrusion molding. The thickness of the orifice plate is 10cm, and the temperature of the molding process is controlled to be 170℃ to obtain the alumina wet strips after pore expansion. Dry in an oven at 110℃ at normal pressure for 2h, and after drying, calcine at 850℃ for 3h to obtain the alumina carrier.
[0057] The pore volume of the alumina carrier is 0.97 mL / g, and the pore volume of pores with a pore diameter of 1 to 15 nm accounts for 81.5% of the total pore volume. The pores with a pore diameter greater than 15 nm are mainly distributed in the range of 100 nm to 200 nm, and the pore volume of pores with a pore diameter of 100 nm to 200 nm accounts for 15.0% of the total pore volume. The mechanical strength of the alumina carrier is 20 N / mm, and the specific surface area is 129 m 2 / g.
[0058] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% molybdenum oxide and 2wt% nickel oxide based on the mass of the carrier.
[0059] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties of the residual oil hydrogenation reaction are shown in Table 1. The hydrogenation reaction conditions are: temperature 380°C, pressure 15MPa, liquid hourly volume space velocity 1h -1 , hydrogen to oil volume ratio 760. The hydrogenation effect is shown in Table 2.
[0060] Example 2
[0061] Weigh 15g of 920DU20 microspheres, the volume fraction of the hydrocarbon core to the volume fraction of the spherical shell of the thermoplastic acrylate polymer is 0.002%. Mix the microspheres with 100g of alumina dry powder and 120g of deionized water and knead them thoroughly. Put the kneaded materials into a high-temperature extruder capable of measuring, cooling and heating the material for extrusion molding. The thickness of the orifice plate is 25cm, and the temperature of the molding process is controlled to be 170℃ to obtain the alumina wet strip after pore expansion. Dry it in an oven at 110℃ at normal pressure for 2h, and after drying, calcine it at 850℃ for 3h to obtain the alumina carrier.
[0062] The pore volume of the alumina carrier is 1.22mL / g, and the pore volume of pores with a pore diameter of 1 to 15nm accounts for 40.1% of the total pore volume. The pores with a pore diameter greater than 15nm are mainly distributed in the range of 100nm to 200nm, and the pore volume of pores with a pore diameter of 100nm to 200nm accounts for 57.5% of the total pore volume. The mechanical strength of the carrier is 12N / mm, and the specific surface area is 100m 2 / g.
[0063] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% tungsten oxide and 2wt% cobalt oxide based on the mass of the carrier.
[0064] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.
[0065] Example 3
[0066] Weigh 3g of 920DU20 microspheres, the volume fraction of the hydrocarbon core to the volume fraction of the spherical shell of the thermoplastic acrylate polymer is 0.004%. Mix the microspheres with 100g of alumina dry powder and 120g of deionized water and knead them thoroughly. Put the kneaded materials into a high-temperature extruder capable of measuring, cooling and heating the material for extrusion molding. The thickness of the orifice plate is 10cm, and the temperature of the molding process is controlled to be 185℃ to obtain the alumina wet strip after pore expansion. Dry it in an oven at 110℃ at normal pressure for 2h, and after drying, calcine it at 850℃ for 3h to obtain the alumina carrier.
[0067] The pore volume of the alumina carrier is 0.95 mL / g, and the pore volume of pores with a pore diameter of 1 to 15 nm accounts for 83.6% of the total pore volume. The pores with a pore diameter greater than 15 nm are mainly distributed in the range of 100 nm to 200 nm, and the pore volume of pores with a pore diameter of 100 nm to 200 nm accounts for 15.9% of the total pore volume. The mechanical strength of the carrier is 20 N / mm, and the specific surface area is 132 m 2 / g.
[0068] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% tungsten oxide and 2wt% nickel oxide based on the mass of the carrier.
[0069] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.
[0070] Example 4
[0071] Weigh 3g of 180DU45 microspheres, the volume fraction of the hydrocarbon core to the volume fraction of the spherical shell of the thermoplastic acrylate polymer is 0.002%. Mix the microspheres with 100g of alumina dry powder, 120g of deionized water, 2g of sesbania powder, and 2ml of nitric acid, and knead them thoroughly. Put the kneaded materials into a high-temperature extruder capable of measuring, cooling, and heating the materials for extrusion molding. The thickness of the orifice plate is 10cm, and the temperature of the molding process is controlled to be 185°C. The alumina wet strips after pore expansion are dried in an oven at 110°C at normal pressure for 2h, and after drying, they are calcined at 850°C for 3h to obtain the alumina carrier.
[0072] The pore volume of the alumina carrier is 0.96 mL / g, pores with a pore diameter of 1 to 15 nm account for 80.5%, pores with a pore diameter greater than 15 nm are mainly distributed in the range of 400 nm to 800 nm, and the pore volume of pores with a pore diameter of 400 nm to 800 nm accounts for 18.2% of the total pore volume. The mechanical strength of the carrier is 18 N / mm, and the specific surface area is 130 m 2 / g.
[0073] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% of molybdenum oxide and 2wt% of cobalt oxide based on the mass of the carrier.
[0074] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.
[0075] Example 5
[0076] Weigh 3g of 920DU20 microspheres, the volume fraction of the hydrocarbon core to the volume fraction of the spherical shell of the thermoplastic acrylate polymer is 0.002%. Mix the microspheres with 100g of alumina dry powder and 120g of deionized water and knead them thoroughly. Put the kneaded materials into a high-temperature extruder capable of measuring, cooling and heating the materials for extrusion molding. The thickness of the orifice plate is 10cm, and the temperature of the molding process is controlled to be 160°C. The alumina wet strips after pore expansion are dried in an oven at 110°C at normal pressure for 2h. After drying, they are calcined at 850°C for 3h to obtain the alumina carrier.
[0077] The pore volume of the alumina carrier is 0.98 mL / g, pores with a pore diameter of 1 to 15 nm account for 68.8%, pores with a pore diameter greater than 15 nm are mainly distributed in the range of 200 nm to 500 nm, and the pore volume of pores with a diameter of 200 nm to 500 nm accounts for 25.9% of the total pore volume. The mechanical strength of the carrier is 16 N / mm, and the specific surface area is 120 m 2 / g.
[0078] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% molybdenum oxide and 2wt% nickel oxide based on the mass of the carrier.
[0079] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.
[0080] Example 6
[0081] Weigh 3g of 920DU20 microspheres, the volume fraction of the hydrocarbon core to the volume fraction of the spherical shell of the thermoplastic acrylate polymer is 0.002%. Mix the microspheres with 100g of alumina dry powder and 120g of deionized water and knead them thoroughly. Put the kneaded materials into a high-temperature extruder capable of measuring, cooling and heating the materials for extrusion molding. The thickness of the orifice plate is 10cm, and the temperature of the molding process is controlled to be 195℃. The alumina wet strips after pore expansion are dried in an oven at 110℃ at normal pressure for 2h. After drying, they are calcined at 850℃ for 3h to obtain the alumina carrier.
[0082] The pore volume of the alumina carrier is 0.97 mL / g, pores with a pore diameter of 1 to 15 nm account for 70.9%, pores with a pore diameter greater than 15 nm are mainly distributed in the range of 200 nm to 500 nm, and the pore volume of pores with a diameter of 200 nm to 500 nm accounts for 26.1% of the total pore volume. The mechanical strength of the carrier is 17 N / mm, and the specific surface area is 122 m 2 / g.
[0083] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% molybdenum oxide and 2wt% nickel oxide based on the mass of the carrier.
[0084] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.
[0085] Comparative Example 1
[0086] Weigh 3g of 920DU20 microspheres, the volume fraction of the hydrocarbon core to the volume fraction of the spherical shell of the thermoplastic acrylate polymer is 0.002%. Mix the microspheres with 100g of alumina dry powder and 120g of deionized water and knead them thoroughly. Put the kneaded materials into a high-temperature extruder that can measure, cool and heat the materials for extrusion molding. The thickness of the orifice plate is 10cm, and the temperature of the molding process is controlled to be 100℃ to obtain the alumina wet strips after pore expansion. Dry in an oven at 110℃ at normal pressure for 2h, and after drying, calcine at 850℃ for 3h to obtain the alumina carrier.
[0087] The pore volume of the prepared alumina carrier is 0.90mL / g, pores with a pore diameter of 1 to 15nm account for 92.9%, pores with a pore diameter greater than 15nm account for 7.1% of the total pore volume, pores with a pore diameter greater than 15nm are mainly distributed in the range of 1μm to 10μm, and the pore volume of 1μm to 10μm accounts for 6.1% of the total pore volume. The mechanical strength of the carrier is 23N / mm, and the specific surface area is 127m 2 / g.
[0088] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% molybdenum oxide and 2wt% nickel oxide based on the mass of the carrier.
[0089] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.
[0090] Comparative Example 2
[0091] Weigh 3g of 920DU20 microspheres, the volume fraction of the hydrocarbon core to the volume fraction of the spherical shell of the thermoplastic acrylate polymer is 0.002%. Mix the microspheres with 100g of alumina dry rubber powder and 120g of deionized water and knead them thoroughly. Put the kneaded materials into a high-temperature extruder capable of measuring, cooling and heating the materials for extrusion molding. The thickness of the orifice plate is 10cm. The temperature of the molding process is controlled at 225°C to obtain the alumina wet strips after pore expansion. Dry them in an oven at 110°C at normal pressure for 2h. After drying, calcine them at 850°C for 3h to obtain the alumina carrier.
[0092] The pore volume of the prepared alumina carrier is 0.90mL / g, pores with a pore diameter of 1 to 15nm account for 93.1%, pores with a pore diameter greater than 15nm account for 6.8% of the total pore volume, pores with a pore diameter greater than 15nm are mainly distributed in the range of 1μm to 10μm, and the pore volume of 1μm to 10μm accounts for 5.5% of the total pore volume. The mechanical strength of the carrier is 23N / mm, and the specific surface area is 127m 2 / g.
[0093] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% molybdenum oxide and 2wt% nickel oxide based on the mass of the carrier.
[0094] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.
[0095] Comparative Example 3
[0096] Weigh 3g of 920DU20 microspheres, the volume fraction of the hydrocarbon core to the volume fraction of the spherical shell of the thermoplastic acrylate polymer is 10%. Mix the microspheres with 100g of alumina dry powder and 120g of deionized water and knead them thoroughly. Put the kneaded materials into a high-temperature resistant extruder that can measure, cool and heat the material for extrusion molding. The thickness of the orifice plate is 10cm, and the temperature of the molding process is controlled to be 170℃ to obtain the expanded alumina wet strips. Dry in an oven at 110℃ at normal pressure for 2h. After drying, calcine at 850℃ for 3h to obtain an alumina carrier. The alumina carrier obtained by extrusion has a fried strip phenomenon, an irregular shape, and visible millimeter holes on the surface. The mechanical strength of the carrier is 8N / mm. The specific surface area is 99m 2 / g.
[0097] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% molybdenum oxide and 2wt% nickel oxide based on the mass of the carrier.
[0098] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.
[0099] Comparative Example 4
[0100] Weigh 3g of acrylonitrile-methacrylonitrile copolymer, 100g of alumina dry rubber powder and 120g of deionized water, mix and knead thoroughly, and put the kneaded materials into a high-temperature resistant extruder capable of measuring, cooling and heating the materials for extrusion molding. The thickness of the orifice plate is 10cm, and the temperature of the molding process is controlled at 170°C to obtain the alumina wet strip after pore expansion. Dry it in an oven at 110°C at normal pressure for 2h, and after drying, calcine it at 850°C for 3h to obtain the alumina carrier.
[0101] The pore volume of the alumina carrier is 0.90 mL / g, pores with a pore diameter of 1 to 15 nm account for 95.1%, pores with a pore diameter greater than 15 nm are mainly distributed in the range of 16 nm to 25 nm, and the pore volume of pores with a pore diameter of 16 nm to 25 nm accounts for 3.1% of the total pore volume. The mechanical strength of the alumina carrier is 25 N / mm. The specific surface area is 131 m 2 / g.
[0102] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% molybdenum oxide and 2wt% nickel oxide based on the mass of the carrier.
[0103] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.
[0104] Comparative Example 5
[0105] Weigh 3g of 920DU20 microspheres, the volume fraction of the hydrocarbon core to the volume fraction of the spherical shell of the thermoplastic acrylate polymer is 0.002%. Mix the microspheres with 100g of alumina dry powder and 120g of deionized water and knead them thoroughly. Put the kneaded materials into a high-temperature extruder capable of measuring, cooling and heating the material for extrusion molding. The thickness of the orifice plate is 0.5cm, and the temperature of the molding process is controlled to be 170℃ to obtain the alumina wet strip after pore expansion. Dry it in an oven at 110℃ at normal pressure for 2h, and after drying, calcine it at 850℃ for 3h to obtain the alumina carrier.
[0106] The pore volume of the alumina carrier is 0.96 mL / g, and the pore volume of pores with a pore diameter of 1 to 15 nm accounts for 82.6% of the total pore volume. The pores with a pore diameter greater than 15 nm are mainly distributed in the range of 100 nm to 200 nm, and the pore volume of pores with a pore diameter of 100 nm to 200 nm accounts for 14.1% of the total pore volume. The mechanical strength of the alumina carrier is 18 N / mm, and the specific surface area is 129 m 2 / g.
[0107] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% molybdenum oxide and 2wt% nickel oxide based on the mass of the carrier.
[0108] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.
[0109] Table 1 Raw oil properties
[0110] nature Raw oil-sand residue <![CDATA[Density (20 °C) / g·cm -3 > 0.9718 S, wt% 3.3 Ni / ppm 22.4 V / ppm 73.7
[0111] Table 2 Hydrogenation effect of the catalyst obtained in each example
[0112] Ni removal rate / % V removal rate / % Example 1 59 85 Example 2 65 93 Example 3 60 85 Example 4 60 88 Example 5 64 92 Example 6 63 92 Comparative Example 1 41 69 Comparative Example 2 43 67 Comparative Example 3 41 75 Comparative Example 4 43 62 Comparative Example 5 54 80
[0113] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. Application of an alumina carrier in residual oil hydrogenation reaction; The preparation method of the alumina carrier comprises the following steps: (1) Mix the aluminum oxide dry glue powder and the microsphere expansion agent evenly; (2) kneading and stabilizing the materials after mixing in step (1); in, The forming equipment is an extruder; the extrusion head of the extruder is a thickened orifice plate; the thickness of the thickened orifice plate is 5cm to 50cm; (3) drying and calcining the molded product obtained in step (2) to obtain an alumina carrier; The microsphere expansion agent in step (1) has a core-shell structure, wherein the outer shell is a thermoplastic acrylic polymer and the inner core is a hydrocarbon; The shell temperature limit of the microsphere expansion agent in step (1) is 155-210° C.; the initial volatilization temperature of the hydrocarbon in the core is 110-145° C.; The volume fraction of the inner core hydrocarbon volume to the outer shell volume is 0.0002% to 0.5%; The temperature of the stable molding process in step (2) should be controlled to be 10°C to 50°C higher than the initial volatilization temperature of the microsphere expansion agent core in step (1); or, the temperature of the stable molding process in step (2) should be controlled to be 5°C to 40°C higher than the temperature limit of the shell of the microsphere expansion agent in step (1); The weight of the microsphere expansion agent added in step (1) is 2% to 30% of the weight of the alumina dry rubber powder; The alumina carrier has a through bimodal pore structure, and the pore volume of the alumina carrier is 0.8-1.3 mL / g; the pore volume of pores with a pore diameter of 1-15 nm accounts for 40%-94% of the total pore volume; the pore volume of pores with a pore diameter of 100-1000 nm accounts for 5%-59% of the total pore volume.
2. The use according to claim 1, characterized in that: The shell temperature limit of the microsphere expansion agent in step (1) is 160-185°C; the initial volatilization temperature of the hydrocarbon in the core is 120-135°C.
3. The use according to claim 1 or 2, characterized in that: The volume fraction of the inner core hydrocarbon volume to the outer shell volume is 0.002% to 0.005%.
4. The use according to claim 1, characterized in that: The microsphere expansion agent in step (1) has at least one of properties A to D: 。 5. The use according to claim 1, characterized in that: The microsphere expansion agent in step (1) has at least one of the properties of E to F: 。 6. The use according to claim 1, characterized in that: The weight of the microsphere expansion agent added in step (1) is 3% to 15% of the weight of the alumina dry rubber powder.
7. The use according to claim 1, characterized in that: The thickness of the thickened orifice plate in step (2) is 10 cm to 30 cm.
8. The use according to claim 1, characterized in that: The temperature of the stable molding process in step (2) should be controlled to be 20°C to 40°C higher than the initial volatilization temperature of the microsphere expansion agent core in step (1).
9. The use according to claim 1, characterized in that: The temperature of the stable molding process in step (2) should be controlled to be 5°C to 25°C higher than the temperature limit of the shell of the microsphere expansion agent in step (1).
10. The use according to claim 1, characterized in that: The pore volume of the alumina carrier is 0.9-1.2 mL / g; the pore volume of pores with a pore diameter of 1-15 nm accounts for 40%-73% of the total pore volume; the pore volume of pores with a pore diameter of 100-1000 nm accounts for 25%-59% of the total pore volume.
11. The use according to claim 1, characterized in that: The mechanical strength of the alumina carrier is 10-30 N / mm.
12. The use according to claim 11, characterized in that: The mechanical strength of the alumina carrier is 12 to 20 N / mm.
Citation Information
Patent Citations
Preparation method of macroporous alumina carrier
CN102861615B
Process for preparation of a catalyst carrier
CN101237927A
Pug uniform extrusion device
CN212445691U